2013
DOI: 10.1055/s-0033-1358734
|View full text |Cite
|
Sign up to set email alerts
|

Elektromyostimulation: Verbesserung von Lebensqualität, Sauerstoffaufnahme und linksventrikulärer Funktion bei chronischer Herzinsuffizienz

Abstract: EMS contributes to an improved quality of life and can improve oxygen uptake and EF in CHF. It may be an alternative therapy in CHF patients who are otherwise unable to undertake conventional forms of exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Our search strategy finally identified twenty-three eligible research articles and (masters) theses (Grützmacher, 2002 ; Vatter, 2003 ; Fritzsche et al, 2010 ; Kemmler et al, 2010a , b , 2012a , 2013 , 2014 , 2015c , d , 2016b , c , d , e , 2017a , b , c ; Kemmler and Von Stengel, 2013 ; van Buuren et al, 2013 , 2014 ; Von Stengel et al, 2015 ; Özdal and Bostanci, 2016 ; Wittmann et al, 2016 ) generated by fourteen research projects numbered and listed in alphabetic order (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search strategy finally identified twenty-three eligible research articles and (masters) theses (Grützmacher, 2002 ; Vatter, 2003 ; Fritzsche et al, 2010 ; Kemmler et al, 2010a , b , 2012a , 2013 , 2014 , 2015c , d , 2016b , c , d , e , 2017a , b , c ; Kemmler and Von Stengel, 2013 ; van Buuren et al, 2013 , 2014 ; Von Stengel et al, 2015 ; Özdal and Bostanci, 2016 ; Wittmann et al, 2016 ) generated by fourteen research projects numbered and listed in alphabetic order (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…(13) In two related NCTs van Buuren et al ( 2013 , 2014 ) reported the effect of WB-EMS vs. locally applied EMS (thigh and gluteals with the same stimulation parameters) on left ventricular function and peak oxygen consumption in patients with CHF. The twice-weekly WB-/EMS protocol was performed for 10 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies could show positive effects of functional electrical stimulation (FES) combined with cycling movement (FES Cycling) [1,2]. Main improvements in stroke patients are motor changes, such as improving walking ability, balance and spasticity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…FES Cycling exercises interventions show significant improvements in cardiorespiratory parameters [9,10]. Investigations with simple electromyostimulation (EMS) without functional movement on cardiac patients with very low cardiac levels also show an increase in cardiorespiratory capacity [2,11]. The relationship between stimulation parameters, functional movement and effects on cardiorespiratory parameters is not yet sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%